THE EFFECT OF FIRM SIZE, CAPITAL STRUCTURE, RETURN ON EQUITY, AND ASSET GROWTH ON DIVIDEND POLICY IN PROCESSED FOOD AND BEVERAGE COMPANIES LISTED ON THE IDX - Cecilia Angeline, Cecilia Angeline; Caryncia Tannia Talib2; Fichella Vanesia; Nova Sitta Tresia Hasugian; Dennys Paulus Parlindungan Damanik; Agung Sahbana (Fakultas Ekonomi Prodi Akuntansi, 2026)
The purpose of this study is to determine the effect of firm size, capital structure, return on equity and asset growth that affect dividend policy, both partially and simultaneously. The study population was 43 beverage and processed food companies from 2019 to 2023. The sample taken was 13 firm with a purposive sampling technique. The analysis method used is multiple linear regression. The results show that only asset growth has a partial effect on dividend policy, while firm size, capital structure, and return on equity have no effect. However, simultaneously all of these factors affect dividend policy.